P-glycoprotein modulates oleanolic acid effects in hepatocytes cancer cells and zebrafish embryos. (5th January 2020) - Kayouka, Maya; Hamade, Aline; Saliba, Eliane; Najjar, Fadia; Landy, David; Greige-Gerges, Hélène
Abstract: Oleanolic acid (OA) is a triterpenoid, widely found in plants and possesses antitumor activity in many cancer lines. However, cancer cells develop multidrug resistance (mdr) hindering the effect of anticancer drugs. P-glycoprotein (P-gp) is a major cause of mdr. Therefore, the cytotoxic effect of OA was evaluated on human breast cancer MDA-MB-231 and human liver cancer HepG2 with absence and presence of P-gp, respectively. OA reduced MDA-MB-231 viability in a dose dependent manner, whereas no remarkable effect was observed on HepG2 in the same range of concentrations (1–60 μM). Moreover, cytotoxicity studies were conducted in the presence of verapamil (20 mg/L), a P-gp inhibitor. OA exhibited the same effect on MDA-MB-231 in the absence and presence of verapamil. However, the cytotoxicity was greatly enhanced for HepG2 cells in the presence of verapamil (cell viability dropped from 63.7% to 25% after 72 h at 60 μM). The results were then confirmed in vivo on zebrafish embryos. Increased mortality and malformations were observed in verapamil pretreated group between 5 and 15 μM of OA compared to control; also, all embryos died at 20 μΜ OA and above. These results demonstrate that inhibiting P-gp enhances the chemotherapeutic activity of OA. Highlights: Oleanolic acid is found in plants and has antitumor activity in many cancer lines. The cytotoxic effect of oleanolic acid was evaluated on MDA-MB-231 and HepG2 cells. Inhibiting P-gp by verapamil enhanced the cytotoxic effect of oleanolic acid. In zebrafish embryos, oleanolic acid was more toxic in the presence of verapamil. Oleanolic acid could be eliminated from cells by the P-gp.